1991
DOI: 10.1111/j.1699-0463.1991.tb01253.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiosis between bacteria isolated from the vagina of women with and without signs of bacterial vaginosis

Abstract: Nagy, E., Petterson, M. & MArdh, P-A. Antibiosis between bacteria isolated from the vagina of women with and without signs of bacterial vaginosis. APMIS 99: 739-744, 1991. Lactobacilli from women with and without bacterial vaginosis (BV) were tested for HzOz production. Thirty-seven (79%) of the 47 strains of lactobacilli isolated from the women without BV produced HzOz, while only nine (23%) of the 39 strains of lactobacilli obtained from women with BV did so. Five of 20 H,O,-producing and two of 26 non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 17 publications
0
32
0
1
Order By: Relevance
“…Boyd et al (2005) found that one third (33 of 97) of strains identified via API 50 CHL were not specifically identified [49]. A discrepancy of the API 50 CHL results and the known original species was also shown by Nagy et al (1991) and Alvarez-Olmos et al (2004) [46,50]. Furthermore, even the APIweb database sometimes caused misidentification or misinterpreted results [49].…”
Section: Identification Methods For Members Of the Genus Lactobacillusmentioning
confidence: 99%
See 1 more Smart Citation
“…Boyd et al (2005) found that one third (33 of 97) of strains identified via API 50 CHL were not specifically identified [49]. A discrepancy of the API 50 CHL results and the known original species was also shown by Nagy et al (1991) and Alvarez-Olmos et al (2004) [46,50]. Furthermore, even the APIweb database sometimes caused misidentification or misinterpreted results [49].…”
Section: Identification Methods For Members Of the Genus Lactobacillusmentioning
confidence: 99%
“…In addition, results of API 50 CHL stripes can show acidification processes instead of growth or fermentation processes and even oxygen or a deviation in the density of the bacterial suspension may affect the output. Misidentification and non-interpretable results are clear pitfalls of this method [46,50]. …”
Section: Identification Methods For Members Of the Genus Lactobacillusmentioning
confidence: 99%
“…Both hydrogen peroxide producers and non-producers showed antibiosis against Mobiluncus spp. 19 (see below).…”
Section: P a T H O G E N I C M E C H A N I S M Smentioning
confidence: 99%
“…6 Moreover, this symbiotic relationship with the production of ammonia would cause a shift to a more alkaline pH, which is inhospitable to lactobacilli. 7 Studies have shown that the addition of anaerobes to a G. vaginalis biofilm enhances the growth of G. vaginalis. 8 These symbiotic relationships could be responsible for the microbiological findings that define BV as well as the typical vaginal signs (Sloughing of the vaginal epithelium visualized as 'clue cells') and amine odor resulting from metabolic by-products of the increased numbers of BVassociated anaerobes.…”
Section: Introductionmentioning
confidence: 99%